THE USE OF ROLE PLAY TO IMPROVE STUDENTS' SPEAKING SKILL - Wulandari wulandari; Dela Octavia Ayuningtias; Yana Yana (IKIP Siliwangi, 2019)
This research entitled the use of Role Play Technique to improve students’ speaking skill. The objective of the research is to improve Speaking skill using Role Play technique. This research used Classroom Action Research. Role play can be trusted to help students speaking ability. The population of the research were the students at SMKN 3 Karawang in Academic years 2017 – 2018. The total population of students in this academic years is 300 Students. The number of sample was 30 students. The data was gathered from test and observation. The average score of test was Cycle I 58.08 and Cycle II 58.06. After the implementation of Role Play activities in every cycle, the students’ speaking score were getting better. It can be seen from the result of students’ average score Cycle I was 83.07 and Cycle II was 77.08. It can be concluded that Role play can improve students’ speaking skill.Keywords: Role play, speaking, CAR